Assessing the responsiveness of the Asthma Quality of Life Questionnaire with pharmaceutical care - Kheir, N.; Emmerton, Lynne; Shaw, J. (Springer, 2008)
Objective: To assess the responsiveness of the Asthma Quality of Life Questionnaire (AQLQ) in the context of pharmaceutical care delivery New Zealand community pharmacy setting. Setting: Community pharmacy practices in three locations in the Otago and Southland region of New Zealand. Method: About 62 patients with asthma (17-80 years of age) were recruited in five community pharmacies in the Otago and the Southland region of New Zealand. Patients were randomly assigned to two groups (Group 1 and Group 2). The AQLQ and a study-specific outcomes questionnaire were administered to both groups at baseline (T1), then again (with an additional global Self-Assessment of change question) 3 months later (at T2) after providing the service to Group 1. Responsiveness of the AQLQ was assessed by measuring the ability of the AQLQ to detect within-subject change in patients who subjectively indicated change, and to distinguish between two groups of patients: those who indicated change and those who indicated no change. Additionally, the correlation between the change of the AQLQ scores at T2 and the patients' self-assessment of change at T2 was estimated and used as means for assessing the AQLQ responsiveness. Main outcome measure: Asthma-specific quality of life as measured by the AQLQ and change in quality of life as perceived by participants. Results: The results supported the responsiveness of three out of the four domains of the Asthma Quality of Life Questionnaire. The fourth domain, Environmental stimuli, showed weaker responsiveness, and the reasons of this were discussed. Conclusion: This study provided data supporting the responsiveness of the AQLQ when used in the context of pharmaceutical care. However, while the AQLQ's Activity Limitation, Symptoms and Emotional domains reflected adequate sensitivity to change in QoL over time, its Environmental domain was less sensitive. Researchers conducting longitudinal studies utilising the AQLQ in pharmaceutical care interventions should bear this in mind, and should consider the possible reasons for this apparent lack of responsiveness, and its implications. © 2007 Springer Science+Business Media B.V.